2019
DOI: 10.3390/ijms20051105
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells as Pathogenetic and Diagnostic Factors, and Potential Targets for GLP-1 in Combination with Metabolic Syndrome and Chronic Obstructive Pulmonary Disease

Abstract: In clinical practice, there are patients with a combination of metabolic syndrome (MS) and chronic obstructive pulmonary disease (COPD). The pathological mechanisms linking MS and COPD are largely unknown. It remains unclear whether the effect of MS (possible obesity) has a major impact on the progression of COPD. This complicates the development of effective approaches for the treatment of patients with a diagnosis of MS and COPD. Experiments were performed on female C57BL/6 mice. Introduction of monosodium g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Our data is in general accordance with previously published results [24]. As in our earlier study [20], this work revealed infiltration of the parenchyma of lungs by inflammatory cells (predominantly macrophages and single neutrophils) in mice of both sexes treated with MSG (Figure 4). At the same time, hemodynamic disturbances and a decrease in the expression of CD31 in the lungs were observed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data is in general accordance with previously published results [24]. As in our earlier study [20], this work revealed infiltration of the parenchyma of lungs by inflammatory cells (predominantly macrophages and single neutrophils) in mice of both sexes treated with MSG (Figure 4). At the same time, hemodynamic disturbances and a decrease in the expression of CD31 in the lungs were observed.…”
Section: Discussionsupporting
confidence: 93%
“…Administration of pegGLP-1 or GLP-1 in cell culture resulted in a decrease of CD31 + endothelial cell apoptosis and an increase in the number of CD34+ cells with active esterases (Figure 9). Thus, it is possible that similar to native GLP-1 [20], CD31 and CD34 positive endothelial progenitor cells are the target for pegGLP-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, sections were staining with hematoxylin and eosin. Histological examination was carried out in three areas of lung tissue (upper, middle and lower) on d21 as described previously [36]. Lung structure, presence of edema, infiltration by proinflammatory cells as well as venous hyperemia, and vascular and bronchial walls thickening were assessed [37][38][39].…”
Section: Histological Examination Of Lung Tissuementioning
confidence: 99%
“…In autoimmune diseases like rheumatoid arthritis or systemic lupus erythematosus, the immune system turns against its own body and triggers inflammation. The International Society for Cellular and Gene Therapies (ISCT) and the International Society for Extracellular Vesicles (ISEV) recognize the potential of extracellular vesicles (EVs, including exosomes) from mesenchymal stromal cells (MSCs) and possibly other cell sources as treatments for OA [16][17][18][19][20][21]. The focus is shifting towards natural alternatives [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%